Family Planning in The Social Fiqh Perspective of K.H. Sahal Mahfudh - Fikriya, Tasya Nailul (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2021)
This study entitled "Family Planning in the Perspective of Social Fiqh KH. MA. Sahal Mahfudh” is the result of literature research to answer the question how did family planning (KB) begin in Indonesia? How Family Planning in the perspective of KH social fiqh. MA. Sahal Mahfudh? How is the istinbath used by KH. MA. Sahal Mahfudh in the discourse of Family Planning (KB). In this study, the authors used a juridical normative approach and legal sociology. The results of this study indicate that Kiai Sahal views family planning as regulating child birth, not eliminating children. This is an effort / human effort to form a family full of maslahah. There are two kinds of social fiqh Kiai Sahal in the law of istinbath: Madzhab Qauli and Madzhab Manhaji. In the context of the KB discourse, namely through the Madzhab qauli and methodological thought (madzhab manhaji) at the same time. Qauli by referring to the hadith of Rasulullah SAW regarding ’azl and he also refers to the opinion of al-Ghazali, Ibn Hajar and Sayyid Sabiq which allow family planning. Then manhaji by considering the benefit. In addition, Kiai Sahal’s opinion about family planning can also be termed the qiyas method, which is analogizing ’azl with family planning tools. According to Kiai Sahal, advances in medical science and technology, especially regarding the development of contraceptive service suggestions, from natural ones, following the calendar to the use of modern contraceptives, condoms, pills, IUDs, are essentially not much different from what is called ’azl. Because the development of social fiqh as exemplified by Kiai Sahal is always based on the principle of caring for the old but still good and relevant and taking the new which is better. In the perspective of Kiai Sahal’s social fiqh, the family planning program is allowed because it aims among others to create quality families of Sakinah, Mawaddah, Wa rahmah and mashlahah families.